Development Of The Nurul Hikmah Islamic Boarding School Website In Ciwidey District Bandung Regency - Dheni Apriantsani Budiman; Feri Alpiyasin; Dani Rohpandi; Susanto Susanto; Hanan Abdul Manan; Yuyus Muttaqin; Danil Akbar Rabbani; Zahira Shofa; Laila Safitri; Santi Nurohmah (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2025)
The advancement of Islamic boarding schools can be improved by using internet-based information media, thereby facilitating widespread community access to information. This phase necessitates sufficient infrastructure that fulfills the institution's requirements. Moreover, creating a website requires specific skills and knowledge to ensure the content is readily accessible, aesthetically pleasing, and comprehensible to consumers. The community service team from STMIK Mardira Indonesia employed a descriptive, qualitative approach in developing the Pondok Pesantren Nurul Hikmah website, using the waterfall model within the Software Development Life Cycle (SDLC) stages. Upon completing the creation process, training is vital for management personnel, especially for operators and administrators who oversee website content. This website development enables the community to get information that is transparent, expedited, and comprehensible.